2024
DOI: 10.1039/d4md00061g
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting thiol-functionalized benzosiloxaboroles for achieving diverse substitution patterns – synthesis, characterization and biological evaluation of promising antibacterial agents

Krzysztof Nowicki,
Joanna Krajewska,
Tomasz M. Stępniewski
et al.

Abstract: Benzosiloxaboroles are emerging class of medicinal agents possessing promising antimicrobial activity. Herein, the expedient synthesis of two novel thiol-functionalized benzosiloxaboroles 1e and 2e is reported. The presence of SH group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…7 Recently, we found that the antibacterial activity of benzosiloxaboroles involves a different mechanism than for related benzoxaboroles pointing to the importance of the introduced structural change. 8 In fact, replacement of the CH 2 with the SiMe 2 group in the oxaborole ring results in increased Lewis acidity and lipophilicity which may be responsible for specic biological activity. Recently, we have also studied crystal structures of functionalized benzosiloxaboroles showing that there is a strong effect of substitution pattern on their supramolecular assembly, mostly manifested by formation of various hydrogen-bonded motifs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Recently, we found that the antibacterial activity of benzosiloxaboroles involves a different mechanism than for related benzoxaboroles pointing to the importance of the introduced structural change. 8 In fact, replacement of the CH 2 with the SiMe 2 group in the oxaborole ring results in increased Lewis acidity and lipophilicity which may be responsible for specic biological activity. Recently, we have also studied crystal structures of functionalized benzosiloxaboroles showing that there is a strong effect of substitution pattern on their supramolecular assembly, mostly manifested by formation of various hydrogen-bonded motifs.…”
Section: Introductionmentioning
confidence: 99%
“…These relatively simple compounds were converted to derivatives bearing 1-arylsulfonyl-1,2,3-triazole-4-yl moiety. Such a structural design was inspired by our previous results showing that arylsulfonamido 17 arylsulfonato, 18 and (bphenylsulfonyl)ethylthio 8 substituted benzosiloxaboroles (Scheme 1, general structures III, IV, and V, respectively) exhibit high activity against the Gram-positive cocci such as methicillin-sensitive Staphylococcus aureus (MSSA), methicillinresistant S. aureus (MRSA), Enterococcus faecalis and Enterococcus faecium. Based on the presented literature background, [10][11][12][13][14][15][16] we assumed that the introduction of 1,2,3-triazole spacer between arylsulfonyl group and benzosiloxaborole might have further positive impact on the antimicrobial potency.…”
Section: Introductionmentioning
confidence: 99%